Evaluation of Radar Reflector Design for Traditional Fishermen in Banyuwangi - Dian Asa Utari; M. Basuki Rahmat; I Putu Arta Wibawa; Arie Indartono; Eko Setijadi; Sri Wiwoho Mudjanarko (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2021)
Every fishing boat owned by fishermen in the Muncar Harbor area of Banyuwangi is always decorated. In addition to beautifying the ship, they also provide enthusiasm for work. Various decorations used include the shape of the dome of the mosque and the shape of a butterfly. Although technically all ornaments do not support their safety at sea. Accidents, namely the collision of traditional fishing vessels by large commercial vessels often occur. because the area of operation of traditional fishermen is the trajectory of large commercial ships. Many accidents occur because the presence of fishing boats is not detected by commercial vessels. because most traditional fishing boats are made of materials that do not reflect the radar signals of large vessels. For this reason, it is very necessary to install a reflector radar, which is a passive radar that serves to increase the object’s Radar Cross Section value. This radar can be mounted on fishing vessels so that the reflected energy from this radar reflector can be recognized by large ships. This article describes designs that are in demand by traditional fishermen in the Muncar area of Banyuwangi.